Fluidized bed technology: it's challenges in industrial applications - Taib, Mohamad Rozainee; Kumoro, Andri Cahyo; Tan, K. G. (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
After fluidized bed technology was first applied in the Winkler process for coal gasification in 1930's, then the development of fluidized bed technology growths very fast. In the recent years, fluidized bed technology has been applied in various industrial processes such as fluid catalytic cracking, gas-solid reaction, drying, particle classification and separation, dedusting, waste treatment, bioprocess etc. The rapid permeation of fluidization technique in Malaysia in the production of chemicals, petroleum and petroleum product, medicine, foods, pharmaceuticals, nuclear, polymers, fertilizer, powder, plastics, metals from their ores and separation, new fine and conventional materials as well as conservation of energy, and disposal of waste and environmental protection etc. has demonstrated its viability in present and future technology of our growing economic construction. However, our expectation to improve the efficiency of the processes has created the need for fresh innovations of the equipment and processes involved, which need adequate understanding of fundamentals. This paper shows several applications of fluidized bed technology in industrial processes and explains the advantages and disadvantages of the process, which offers innovation touch to obtain better result.